2002
DOI: 10.1128/cdli.9.6.1332-1337.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Presence of Chlamydia pneumoniae in Cerebrospinal Fluid of Patients with Clinically Definite and Monosymptomatic Multiple Sclerosis

Abstract: There is considerable controversy concerning the evidence for the presence of Chlamydia pneumoniae in the cerebrospinal fluid (CSF) of both multiple sclerosis (MS) patients and patients with other neurological diseases (OND). In order to clarify this issue, the laboratories at Vanderbilt University Medical Center (VUMC) and the University of South Florida (USF) examined the reproducibility of their respective PCR assays for the detection of C. pneumoniae DNA in the CSF of a common group of MS patients and OND … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…We and others have suggested that C. pneumoniae may act as a co-factor in the disease [1,3,4]. Other groups have confirmed our observations on the PCR based assays for the detection of C. pneumoniae in the CSF while some have not [5][6][7][8][9][10][11][12][13]. These inconsistencies might be due to methodological differences in the isolation and detection of the C. pneumoniae organism and DNA that are unlikely to be reconciled without some consensus regarding current methods or the development of better technology [14].…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…We and others have suggested that C. pneumoniae may act as a co-factor in the disease [1,3,4]. Other groups have confirmed our observations on the PCR based assays for the detection of C. pneumoniae in the CSF while some have not [5][6][7][8][9][10][11][12][13]. These inconsistencies might be due to methodological differences in the isolation and detection of the C. pneumoniae organism and DNA that are unlikely to be reconciled without some consensus regarding current methods or the development of better technology [14].…”
Section: Introductionsupporting
confidence: 83%
“…The PCR assay to detect C. pneumoniae MOMP DNA, was done using a nested PCR assay as described previously using similar running conditions [11].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, CSF detection of heat-shock protein-60 messenger RNA (Hsp-60 mRNA) and 16S rRNA by Reverse-Transcriptase PCR (RT-PCR) was more frequent in MS patients than in controls signifying the presence of a high rate of gene transcription and, therefore, more active metabolism of C. pneumoniae in MS (Dong-Si et al, 2004). Conflicting findings were also obtained in two recent collaborative studies involving different laboratories in which the presence of C. pneumoniae was evaluated in blinded CSF samples, further underlining the lack of an accepted standardized PCR protocol (Kaufman et al, 2002;Sriram et al, 2002). In this context, we have recently studied a group of patients with MS, other inflammatory neurological disorders (OIND) and non-inflammatory neurological disorders (NIND) in whom a PCR positivity for MOMP and 16S rRNA in CSF was present in a small proportion of MS (37%), OIND (28%) and NIND (37%) patients, without any differences between MS and controls.…”
Section: Pcr Studiesmentioning
confidence: 90%
“…We recognize the problems inherent in using nested PCR assays. To increase the specificity of our nucleic acid-based amplification assays, we required amplification with primers for 2 different C. pneumoniae genes to designate a sample as positive [4].…”
Section: Reply To Hammerschlag Et Almentioning
confidence: 99%